Sentiment Change and Negative Herding: Evidence from Microblogging and News - Dong, Hang; Kim, Ji Kyung (Jeanne); Choi, Jeonghye; Chang, Sue Ryung (Elsevier, 2022)
Companies deal with good and bad publicity daily. We study the impact of news on consumer sentiment toward a company in the presence of pre-news sentiment. We use Sina Weibo’s (the Chinese version of Twitter) microblogging data and the full list of news items published in Sina Finance between 2013 and 2014 to measure sentiment. In our study, we address the following research questions: Does negative news have a greater impact than positive news on consumer sentiment change? Does news affect sentiment change to a greater degree when pre-news sentiment matches the news valence? Does the type of company (either B2C or B2B) matter? Our empirical findings show that consumers overreact to negative news and negative pre-news sentiment intensifies such overreaction, leading to negative herding. Further, negative pre-news sentiment is even more damaging for B2B companies than for B2C companies.
Keywords: consumer sentiment; negativity effect; herd behavior; negative herding; microblogging; B2C versus B2B; 53 Ciencias Económicas::5308 Economía general::5308.02 Comportamiento del consumidor; ODS 8 - Trabajo decente y crecimiento económico; ODS 9 - Industria, innovación e infraestructura; ODS 12 - Producción y consumo responsables